2020
DOI: 10.30597/mkmi.v16i3.9048
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberdayaan Wanita terhadap Pemilihan Penolong Persalinan pada Tenaga Kesehatan Terampil

Abstract: Angka Kematian Ibu (AKI) di Indonesia tahun 2015 diperkirakan sebesar 305 kematian per 100,000 kelahiran hidup. Upaya besar perlu dilakukan untuk mencapai target SDGs pada tahun 2030, yaitu 70 kematian maternal. Peningkatan otonomi dan pemberdayaan wanita diharapkan mampu meningkatkan peran wanita dalam keputusan terkait dengan kese-hatannya. Penelitian ini bertujuan untuk menunjukkan pengaruh pember-dayaan wanita terhadap pemilihan penolong persalinan pada tenaga kesehatan terampil, dengan menggunakan data SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…So that mothers must get antenatal care (ANC) services that are by the standards, which is to carry out three examinations, namely the 1st, 2nd and 3rd trimesters with health workers in health facilities The risk of mothers who are socioeconomic in the lowest quartile (quartile 1) to give birth to non-health workers is 6.4 times higher than that of mothers who are socioeconomic in the top quartile of wealth after controlling for other maternal variables. This finding is in line with the results of previous research from Wulandari et al (2020), namely the economic status of the household also plays a role in the selection of birth attendants. Women who have a household economy in quintile 1 (lowest) give birth to non-skilled health workers.…”
Section: Multivariate Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…So that mothers must get antenatal care (ANC) services that are by the standards, which is to carry out three examinations, namely the 1st, 2nd and 3rd trimesters with health workers in health facilities The risk of mothers who are socioeconomic in the lowest quartile (quartile 1) to give birth to non-health workers is 6.4 times higher than that of mothers who are socioeconomic in the top quartile of wealth after controlling for other maternal variables. This finding is in line with the results of previous research from Wulandari et al (2020), namely the economic status of the household also plays a role in the selection of birth attendants. Women who have a household economy in quintile 1 (lowest) give birth to non-skilled health workers.…”
Section: Multivariate Analysissupporting
confidence: 92%
“…Then the greater the wealth quintile, which means that the higher a person's economic status, the smaller the percentage of women who give birth with the help of non-skilled health workers. [9]. Other studies show that pregnant women who do not have or prepare for delivery costs have a 1.7x greater chance of choosing birth attendants by non-health workers than pregnant women who do prepare for their delivery costs [12].…”
Section: Multivariate Analysismentioning
confidence: 99%
See 2 more Smart Citations
“… 29 Previous studies in Indonesia showed that women living in urban areas were less likely to choose delivery with the help of TBAs than women living in rural areas (p≤0.001; OR 0.70; 95% C 0.60 to 0.91). 22 Due to strong cultural beliefs, accessibility and availability of delivery facilities (long distance to health facilities), rural residents trust TBAs more than health professionals and prefer to give birth in non-health facilities or at home, regardless of the competence of birth attendants. 23 Living in urban areas allows for easier access to health facilities and information than living in rural areas.…”
Section: Discussionmentioning
confidence: 99%